2021
DOI: 10.1108/itp-03-2021-0225
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effect of technology overload on the ability of online learning to meet students' basic psychological needs

Abstract: PurposeMost students are considered digital natives and are presumably equipped to handle extensive technology use. However, online learning turns students into involuntary telecommuters when it is the primary modality. The prevailing trends of online learning, digital socialization, telehealth and other online services, combined with remote work has increased students' reliance on information and communications technologies (ICTs) for all purposes, which may be overwhelming. We examine how technology overload… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 58 publications
(80 reference statements)
0
7
0
Order By: Relevance
“…Technology acceptance and adoption also have a crucial role in platform success. Recently, personal innovativeness in information technologies has been investigated as a moderator of relevant relationships (Abubakre et al, 2020) and also the moderating role of technology and how it can strengthen satisfaction has been studied in different contexts (James et al, 2021). Also, technology experience has received attention demonstrating a strong influence of personal innovativeness (Thompson et al, 2006), and the perceived ease of use has been found to be a critical element for technology adoption (Venkatesh et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Technology acceptance and adoption also have a crucial role in platform success. Recently, personal innovativeness in information technologies has been investigated as a moderator of relevant relationships (Abubakre et al, 2020) and also the moderating role of technology and how it can strengthen satisfaction has been studied in different contexts (James et al, 2021). Also, technology experience has received attention demonstrating a strong influence of personal innovativeness (Thompson et al, 2006), and the perceived ease of use has been found to be a critical element for technology adoption (Venkatesh et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In the sampled articles, quantitative analysis predominates the overall analysis technique. Structural Equation Model leading the analysis technique either using the Covariance-Based Structural Equation Model (CB-SEM) [25,43,50,[58][59][60][61][62][63] or the Partial-Least Square Structural Equation Model (PLS-SEM) [14,21,42,64,65]. Other quantitative analysis such as regression [66,67], correlation [39,44,68], and ANOVA [17,18,69,70] were also implemented in the sampled research.…”
Section: Research Approaches and Statistical Analysismentioning
confidence: 99%
“…Nevertheless, what is known from past research is that basic psychological needs satisfaction may moderate the relationship between ICT use and emotion ( Allen and Anderson 2018 ; Przybylski et al 2009 ; Fang et al 2019 ; James et al 2022 ; Partala and Kallinen 2012 ; Pettersson et al 2021 ). For example, Przybylski et al ( 2009 ) found that when people’s basic psychological needs are satisfied, they will have a better experience when playing games on ICT; however, when their satisfaction with basic psychological needs is low, they will experience negative emotions such as stress when playing games with ICT.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Przybylski et al ( 2009 ) found that when people’s basic psychological needs are satisfied, they will have a better experience when playing games on ICT; however, when their satisfaction with basic psychological needs is low, they will experience negative emotions such as stress when playing games with ICT. James et al ’s ( 2022 ) study indicated that people who are satisfied with their basic psychological needs promote their positive learning emotions when learning with ICT, while people with unsatisfied basic psychological needs are more likely to experience learning anxiety when they use ICT to learn.…”
Section: Introductionmentioning
confidence: 99%